ASSOCIATION BETWEEN PEMPHIGUS AND PSORIASIS: A SYSTEMATIC REVIEW - Sari Dabukke, Yeyen Jani (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Pemphigus vulgaris, foliaceus, paraneoplastic, IgA, and herpetiformis are autoimmune bullous diseases. Epidemiologically heterogeneous symptoms characterize pemphigus. The first non-HLA genes related with PV have been found, and our knowledge of pemphigus frequency, which varies widely between populations, has increased. Pemphigus causes blisters and lesions. This polymorphism is also linked to many comorbidities, including autoimmune illnesses, hematological malignancies, and psoriasis. Psoriasis is a T cell-mediated papulosquamous skin illness that results from immune system dysregulation. It is characterized by severe inflammatory and hyperproliferative alterations in the affected areas of the skin. Psoriasis has traditionally been linked to bullous pemphigoid, which is a subepidermal autoimmune bullous illness. Pemphigus is a group of IgG-mediated blistering diseases that affect the skin and mucous membranes' squamous epithelium. Pemphigus causes painful intraepidermal blisters and erosions. Pemphigus disease is chronic and autoimmune, which has increased research into its link with other autoimmune and autoinflammatory disorders. Pemphigus and psoriasis have been reported to co-occur, however their relationship is uncertain. Yet, there are also additional biological plausible reasons for this link. The "epitope spreading phenomena" may have caused the disease. This occurs when a primary autoimmune or inflammatory response damages tissue. Hence, the immune system can now detect some protein components, triggering a subsequent autoimmune reaction. Psoriasis patients are three times more likely to develop pemphigus. Psoriasis doctors should know about this epidemiological trend.